Assessment of running gear performance in relation to rolling contact fatigue of wheels and rails based on stochastic simulations. (April 2020) - Six, Klaus; Mihalj, Tomislav; Trummer, Gerald; Marte, Christof; Krishna, Visakh V; Hossein-Nia, Saeed; Stichel, Sebastian
In this work, the authors present a methodology for assessing running gear with respect to rolling contact fatigue of wheels and rails. This assessment is based on the wheel/rail contact data of different wheel profile wear states obtained from a wheel profile prediction methodology. The approach allows a cumulative assessment of the rolling contact fatigue of rails in different curve radii (e.g. the sum of damage over the lifetime of wheel profiles). Furthermore, the assessment of the rolling contact fatigue can be undertaken at different wear states of the wheel profiles to provide an insight on how the rolling contact fatigue of wheels and rails varies depending on the evolution of wheel wear. The presented methodology is exemplarily applied to two bogie types, the UIC-Y25 standard bogie and the so-called FR8RAIL bogie with a mechanical wheelset steering device. The presented methodology has been shown to be a useful tool for the optimisation of vehicles already in an early stage of the vehicle development process.